An overview of Palaeoeskimo architectural remains in the Central Canadian Low Arctic - Ryan, Karen (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper presents an overview of the architectural remains associated with the Palaeoeskimo occupations of the Central Canadian Low Arctic. Palaeoeskimos inhabited this area for approximately 4,000 years which have be divided by archeologists have identified nine chrono-cultural periods: Early Palaeoeskimo (Pre-Dorset, Transitional Pre-Dorset/Dorset, Lagoon, and Groswater) and Late Palaeoeskimo (Early, Middle, Late, and Terminal Dorset, as well as Choris). While the validity of these divisions remains contentious, research throughout the region has documented significant architectural variability within and between these cultural groups. This paper proposes a typological system for the description and organization of the architectural remains currently reported in order to facilitate renewed discussion of the underlying causes of Palaeoeskimo architectural variability.